Pemberian Makanan Tambahan pada Ibu Hamil KEK di Puskesmas Karya Wanita Pekanbaru - Mita Puspitasari; Mitra Mitra; Tin Gustina; Zulfayeni Zulfayeni; Novita Ranyin (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Chronic Energy Deficiency in pregnant women is a condition of pregnant women due to an imbalance in the intake of energy and protein nutrients, so that the substances the body needs are not fulfilled. Incident chronic energy deficiency in pregnant women have a risk of abortion, bleeding, prolonged labor, infection, low birth weight baby, birth defects, and causes of death indirectly. An attemt to resolve the incidence of malnutrition in pregnant women in chronic energy deficiency with supplementary food. Type of qualitative research. Research informants were pregnant women chronic energy deficiency, nutrition staff, midwives, health promotion officers, and cadres. Research results are the knowledge of pregnant women in chronic energy deficiency about supplementary feeding is stil lacking, the attitudes of pregnant women in chronic energy deficiency and their husband’s support about supplementary feeding are already good, compliance of pregnant women in chronic energy deficiency is still lacking, acceptance of pregnant women in chronic energy deficiency about supplementary feeding is stil lacking, delivery of information when counseling needs to be improved by using the contemporary method, distribution of supplementary feeding for Puskesmas officers in collaboration with cadres. Advice doing technical guidance to health workers about supplementary feeding, health workers increase again in providing information related to supplementary feeding, provide information using digital media such as video, made a special trick of setting an alarm as a reminder to consume supplementary feeding, make derivate technical guidelines from the ministry of helath according to conditions in the field.